PSYCHOLOGICAL AND QUALITY OF LIFE SCALE SCORES CORRELATED WITH THE WINTER INCREASE OF AMBULATORY BLOOD PRESSURE IN PATIENTS WITH ARTERIAL HYPERTENSION. (June 2022) - Andreeva, Galiya; Deev, Alexander; Gorbunov, Vladimir
Abstract : Objective: The aim of study was to define correlations between winter blood pressure (BP) increase and psychological, quality of life (QL), demographic factors in patients with arterial hypertension (AH) (Moscow region). Design and method: We assessed 980 ambulatory blood pressure monitoring (ABPM) data AH patients without serious concomitant diseases. ABPM monitor (Spacelabs 90207) was applied after the washout period (at 8.30–12.00 am). We defined daytime period as 8.00–22.00, nighttime – 0.00–6.00, evening – 21.00–23.00, morning – 6.00–8.00 and workplace period as 11.00–19.00. After ABPM session patients completed the QL questionnaire. (J.Siegrist et all.). The systolic and diastolic (SBP and DBP) winter increase BP was assessed for: daytime (BPd), nighttime (BPn), evening (BPe), morning (BPm), workplace (BPw) and 24-hours period (BP24). We used General Linear Model (GLM) Procedure for statistical analysis adjustment for age, sex and duration of AH and Fisher's (F) test. Results: We have identified the following QL factors that were significantly associated with the SBP winter increase: 1) VI scale scores of QL questionnaire (reflects the level of social support of family, friends, colleagues) with SBPn (F = -6, 62 p < 0, 01), SBPd (F = -11, 12, p < 0, 001), SBPw (F = -9, 33, p < 0, 003), SBPm (F = -10, 59 p < 0, 001), SBPe (F = -5, 4, p < 0, 02); 2) IV scale scores (negative psychological well-being) with SBPw (F = 9, 33, p < 0, 003). The following factors were significantly associated with the DBP winter increase: 1) VI scale scores with DBPd (F = 4, 06, p < 0, 04), SBPm (F = 4, 29 p < 0, 004). Thus, such QL components as the social support from family, friends, colleagues, (VI scale scores) and the negative emotions (IV scale scores) have been associated with the winter BP increase (negative and positive correlation respectively). Conclusions: The new preventive strategy for reducing winter BP may include the increase communication with family and friends and to reduce the impact of negative emotions in the workplace in Moscow region patients with AH.